2022
DOI: 10.1002/kjm2.12501
|View full text |Cite
|
Sign up to set email alerts
|

Lysine demethylase 5C epigenetically reduces transcription of ITIH1 that results in augmented progression of liver hepatocellular carcinoma

Abstract: Lysine demethylase 5C (KDM5C) is a member of the KDM family of demethylases and has been reported as a cancer driver. This study aimed to probe the function of KDM5C in the development of liver hepatocellular carcinoma (LIHC) and the molecules of action. According to data from publicly accessible bioinformatic databases, KDM5C is highly expressed in LIHC and associated with poor patient prognosis. High expression of KDM5C was detected in acquired LIHC cell lines. Downregulation of KDM5C weakened proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a recent study, KDM5C was significantly upregulated in HCC in vitro, and silencing of KDM5C reduced the malignant behaviors of the cell lines and inhibited tumor growth in nude mice. KDM5C promoted HCC development by epigenetically downregulating inter-alpha-trypsin inhibitor heavy chain 1 ( ITIH1 ) and thereby activating the PI3K/AKT pathway [ 42 ]. Another study indicated that KDM5C could facilitate cell migration, invasion, and epithelial–mesenchymal transition in HCC by inhibiting bone morphogenetic protein 7 ( BMP7 ) expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, KDM5C was significantly upregulated in HCC in vitro, and silencing of KDM5C reduced the malignant behaviors of the cell lines and inhibited tumor growth in nude mice. KDM5C promoted HCC development by epigenetically downregulating inter-alpha-trypsin inhibitor heavy chain 1 ( ITIH1 ) and thereby activating the PI3K/AKT pathway [ 42 ]. Another study indicated that KDM5C could facilitate cell migration, invasion, and epithelial–mesenchymal transition in HCC by inhibiting bone morphogenetic protein 7 ( BMP7 ) expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%